Rabbit metabolic response and selected meat quality traits: Evaluation of dietary PLX®23 and LycoBeads® feed supplement. Issue 1 (25th October 2018) - Palazzo, Marisa; Schiavitto, Michele; Cinone, Mario; Vizzarri, Francesco
Abstract: Effects of dietary supplementation of verbascoside and lycopene, alone and in combination, on some blood parameters, plasma oxidative status and meat quality traits in intensively reared rabbits were investigated. The test lasted 60 days and was conducted on 200 weaned‐rabbits, divided into four groups of 50 animals each (5 animals each cage × 10 repetitions). The control group (CON) received a fattening feed without any feed supplements, whereas the experimental groups received the following: the first, an integration in 22 g of PLX ® 23 ( Lippia citriodora extract; VB group) per ton of feed; the second, an integration in 100 g of LycoBeads ® ( Solanum lycopersicum extract; LIC group) per ton of feed; and the third, an integration of both feed supplements in combination at the same doses (LIC+VB group). The dietary supplementation with Lippia citriodora and Solanum lycopersicum resulted in an improvement of the blood lipid profile, oxidative plasma markers, and hepatic and renal activity of treated growing rabbits. Feed additives also produced meat with a lower content in SFA and an increased PUFA content, and inhibited the lipid oxidation improving the oxidative stability of rabbit meat. The dietary supplementation, even reporting no effects on productive parameters and carcass yield, showed an improvement on several blood parameters, as indicator of animal welfare, and on quality and healthy meat markers.